THE EFFECTIVENESS OF MASSAGE EFFLEURAGE THERAPY TOWARDS DECREASE DYSMENORRHEA IN ADOLESCENT - Mariene Wiwin Dolang (Stikes Graha Edukasi Makassar, 2019)
Introduction: Adolescence is a transition from children to adults. where one of the characteristics is the occurrence of menstruation. During menstruation there are sometimes gynecological problems that are often complained of by adolescents, such as dysmenorhea. Dysmenorrhea can result in disruption of activities that can be overcome by using pharmacological and non-pharmacological methods, one of which is Masase effleurage. The purpose of this study was to analyze the differences in the intensity of menstrual pain before and after the administration of effase massage therapy to female students at MTs Muhammadiyah Hatu Putih Manipa. Methods: design method used in this study was a pre-trial design with one group pre-post test design. The population in this study were all students of MTs Muhammadiyah Hatu Putih Manipa. Sampling in this study using a total sampling technique. The sample in this study was students of MTs Muhammadiyah Hatu Putih Manipa which counted 42 people. Results: The results showed that there was support for message effleurage therapy to reduce menstrual pain in adolescents (p = 0,000, Mean Pre =5,71,Mean Post = 2,74). Conclusion: The conclusion in this study is related to the delivery of effleurage message therapy to decrease menstrual management in adolescents. For adolescents, it is recommended to use effleurage massage therapy in the management of menstrual pain because it is easier, cheaper, efficient, and can be done independently.